Peran Trust in Government dan Tax elektronik sistem dalam meningkatkan kepatuhan wajib Pajak Generasi Milenial: The Role of Trust in Government and Electronic Tax Systems in Increasing Tax Compliance of Millennial Generation - Aliy Rasyid; Abdillah; Muhammad Bayu Seto Kencono (OGZ Research & Publishing, 2025)
Objective: This study aims to analyze the role of Trust in Government and the electronic tax system in improving millennial taxpayer compliance.Methodology: Data were collected through questionnaires distributed to 100 millennial taxpayer respondents registered at the North Cikarang Tax Office (KPP Pratama) using a purposive sampling technique. Data analysis was conducted using validity tests, reliability tests, simple linear regression, and t-tests.Research Results: The results showed that Trust in Government significantly influenced millennial taxpayer compliance, while the electronic tax system had no significant effect on taxpayer compliance. This indicates that the level of trust in the government has a more dominant influence on millennial tax compliance than the use of electronic systems, which are considered standard.Keywords: Trust in Government, Electronic Tax System, Taxpayer Compliance